Dampak COVID-19 (Coronavirus Disease 2019) Terhadap Proses Pembelajaran dan Psikologis Bagi Siswa - Dea Nur Eka Mutiara (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
The COVID-19 disease was first discovered in Wuhan, China, caused by a virus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) which eventually led to Coronavirus Disease-2019 (COVID-19). This virus is a type of virus that is contagious, the transmission itself comes from people with COVID-19 when coughing or sneezing which emits small droplets, which then stick to surrounding objects. This disease can infect anyone and there is no age limit, but older people and people who have a previous history of diseases (such as diabetes, asthma, other respiratory problems) will be prone to getting worse. diseases (such as diabetes, asthma, other respiratory problems) will be prone to getting worse. The day the spread of COVID-19 is getting higher in various countries, this has a huge impact on the economic system in various countries. In addition, it also has an impact on the world of education, because it causes the learning system to be disrupted and even temporarily closes. This is very influential on the psychology of students, because learning is less effective and not optimal in the activities carried out.